ENSAMBLE MUSIK SEKOLAH “TANAH AIR” - Indra Nugraha Pratama; Harisnal Hadi; Erfan Erfan (SENDRATASIK UNP, 2018)
Abstract School Music Ensamble “Tanah Air” aims to apply the science of music art education and teach it to the students of madrasah aliyah in playing musical instruments in the concept of ansamble music. The shape of the plots of these works of art in stacking pattern ansamble format games percussion instruments and melodies of the Tanah Air songs played with pianika, bellyra, bass drum, cymbals, snare drum, qwintom and coupled with dance using the attribute flag. In the process of making this work is done with three stages, namely, the phase of exploration, experimentation, and forming. This work is done with a simple arrangement and not too complex for easy taught to elementary school students who is a beginner in playing an instrument. Keywords: School Music Ensamble “Tanah Air”.